Odontophrynus barrioi, a New Species of Anuran from Argentina - Cei, José Miguel Alfredo María (1982)
A new species of Odontophrynus from 2200 m altitude in the Sierra de Famatina, Argentina, is described. Morphological as well as cytogenetic features differentiate the new species, O. barrioi, from the populations of the O. occidentalis group.